Learning from data an introduction to statistical reasoning - Glenberg, Arthur M. (Lawrence Erlbaum Associates, 2008)
Focuses on how to interpret psychological data and statistical results. This book uses repetition to enhance students' memories with multiple examples, reintroductions of the major concepts, and a focus on these concepts in the problems. It is suitable for undergraduate or beginning graduate statistics courses in psychology and education